1990
DOI: 10.1063/1.104118
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface heating effects during pulsed laser evaporation of materials

Abstract: We have theoretically and experimentally investigated the thermal effects of targets evaporated by nanosecond laser pulses. The subsurface temperatures were calculated to be higher than the surface temperatures during planar surface evaporation of the target material. While the evaporating surface is being cooled due to the latent heat of vaporization, subsurface superheating occurs due to a finite absorption depth of the laser beam. The temperature profiles of silicon targets irradiated by nanosecond laser pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(32 citation statements)
references
References 9 publications
2
29
0
1
Order By: Relevance
“…This decrease is related to morphological changes which could be fundamentally determined by the rapid crystallization of the surface in case a liquid exists. The fact that we find, precisely for this energy density valué, a final decrease of the reflectance, agrees with the proposed valué estimates in (3).…”
Section: Real Time Reflectancesupporting
confidence: 80%
“…This decrease is related to morphological changes which could be fundamentally determined by the rapid crystallization of the surface in case a liquid exists. The fact that we find, precisely for this energy density valué, a final decrease of the reflectance, agrees with the proposed valué estimates in (3).…”
Section: Real Time Reflectancesupporting
confidence: 80%
“…5) showed that when the surface reached the melting temperature, the thermal gradient near the surface region was much steeper for the excimer than for the Nd:YAG heated material. According to the model of R. K. Singh et al [25], such a small thermal gradient coupled with a low absorption coefficient can result, when the evaporation begins, in strong subsurface heating and lead to microexplosions. Unfortunately, the optical and thermo-physical constants of liquid ZnO have not yet been measured, so it is not possible to accurately check the model predictions.…”
Section: Resultsmentioning
confidence: 99%
“…The bigger particles are thought to come from the target as a result of microcracks, pits and weakly attached particles. The submicron particles are due to the superheating of the subsurface region [46], which reaches a higher temperature than the surface, cooled by the latent heat of evaporation. In this latter case the gaseous phases nucleate and cause volume expansion which leads to explosive sublimation.…”
Section: Discussionmentioning
confidence: 99%
“…First we have to note that the problem of particulate coming from the target is inherent in the ablation processes [43,44]. Commonly one observes two classes of particulate roughly distinguished in over-micron round shaped particles and submicron round or faceted particulate [45,46]. The bigger particles are thought to come from the target as a result of microcracks, pits and weakly attached particles.…”
Section: Discussionmentioning
confidence: 99%